Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/jom.0000000000001290
|View full text |Cite
|
Sign up to set email alerts
|

Total Worker Health® Intervention for Construction Workers Alters Safety, Health, Well-Being Measures

Abstract: A TWH intervention tailored for construction crews can simultaneously improve safety, health, and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…A final comment is that the nature of the pandemic, affecting society as a whole, seems to be helping to push through change management, acceptance, and adoption of change at a much faster rate than normally experienced with construction health and safety initiatives. While research has established the link between taking work‐related safety back to home life (Anger et al, 2018; Fleming, 2001), this may be an example of safety in the home (and wider society) taking safety into the workplace.…”
Section: Observation 1: Managing Covid‐19 Risk In Constructionmentioning
confidence: 99%
“…A final comment is that the nature of the pandemic, affecting society as a whole, seems to be helping to push through change management, acceptance, and adoption of change at a much faster rate than normally experienced with construction health and safety initiatives. While research has established the link between taking work‐related safety back to home life (Anger et al, 2018; Fleming, 2001), this may be an example of safety in the home (and wider society) taking safety into the workplace.…”
Section: Observation 1: Managing Covid‐19 Risk In Constructionmentioning
confidence: 99%
“…Our program evaluation results indicated that leaders were commonly working on foundational goals related to TWH policy and program development that may need time to implement [ 22 ]. In contrast to our intervention, most other TWH-related and safety-specific intervention studies that include leadership focus on supervisors and changes in outcomes amongst their teams within a few weeks or months with mixed findings [ 12 , 13 , 15 , 16 , 18 , 19 , 43 46 ].…”
Section: Discussionmentioning
confidence: 91%
“…Our research, and that of others, suggests that small business owners and other senior leaders are a key target audience for interventions as their actions are significantly related to business and employee TWH practices [ 27 30 ]. While TWH interventions with leadership components hold promise as methods to change organizational behavior with ultimate effects on workforce outcomes [ 16 , 18 ], the interventions have been traditionally focused on supervisor level leadership behaviors. Supervisors are key to the implementation of the TWH approach on a day-to-day basis.…”
Section: Introductionmentioning
confidence: 99%
“…Research supports the potential of integrated workplace approaches to improve worker health, safety, and well-being by addressing overlapping risk factors [43,44,45]. While evaluating the impacts of TWH framework is an emerging field, several studies have shown that TWH interventions can effectively address injuries and chronic diseases in specific worker populations [46,47,48,49,50]. While the current study did not evaluate specific integrated TWH interventions or programs, in our 2016 survey we found that only 15.6% of worksites reported a coordinated program for occupational health and safety with health promotion (data not shown).…”
Section: Discussionmentioning
confidence: 99%